Effective Cough Management Due to Pulmonary Tuberculosis - Irpan Ali Rahman (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Tuberculosis is a public health problem worldwide, with Indonesia, in particular, being the second leading cause of death from infectious diseases. Objective: Carry out comprehensive nursing care to clients experiencing respiratory system disorders due to Pulmonary TB with effective cough interventions. Method: The study's design uses a case study to describe the phenomenon with a nursing care approach. Results: Showing clients said frequent coughs at night, coughing up phlegm, and difficulty removing phlegm are the causes of this. Pulmonary TB results in primary infection of the alveoli, increased secretion production, and ineffective airway clearance problems. Conclusion: Optimizing airway management in pulmonary tuberculosis nursing care with airway clearance is ineffective